2011
DOI: 10.2174/156800911798073023
|View full text |Cite
|
Sign up to set email alerts
|

Effective Treatment of Human Lung Cancer by Targeting Tissue Factor with a Factor VII-Targeted Photodynamic Therapy

Abstract: Lung cancer is the leading cause of cancer death. Conventional photodynamic therapy (PDT) using a nontargeted photosensitizer (ntPDT) is a treatment option for central- and peripheral-type early-stage lung cancer. However, ntPDT can cause severe side effects for normal tissue due to its non-selective distribution. To improve the selectivity and effectiveness of ntPDT for human lung cancer, we hypothesized that tissue factor would be a common yet specific biomarker and a potential therapeutic target for both lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
60
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(63 citation statements)
references
References 68 publications
(163 reference statements)
3
60
0
Order By: Relevance
“…Thus we conclude that TF is a common yet specific biomarker and therapeutic target molecule for both the tumor cells and tumor neovasculature [10][11][12]17,18]. By choosing the receptor TF as a target molecule and using its natural ligand, coagulation factor VII (fVII), as a targeting vehicle, we have successfully developed a novel dtPDT, namely fVII-targeted PDT (fVII-tPDT) using fVII-SnCe6 (activation wavelength at 635 nm) or fVII-VP (activation wavelength at 689 nm) conjugates, for treatment of human breast [12,17,18] and lung cancer [11] and wet macular degeneration [19] in preclinical studies. Our results showed that fVII-tPDT was selective and effective in vitro in killing angiogenic vascular endothelial cells and tumor cells that express TF as well as in vivo in treating breast and lung tumor xenografts in mouse models.…”
mentioning
confidence: 78%
See 3 more Smart Citations
“…Thus we conclude that TF is a common yet specific biomarker and therapeutic target molecule for both the tumor cells and tumor neovasculature [10][11][12]17,18]. By choosing the receptor TF as a target molecule and using its natural ligand, coagulation factor VII (fVII), as a targeting vehicle, we have successfully developed a novel dtPDT, namely fVII-targeted PDT (fVII-tPDT) using fVII-SnCe6 (activation wavelength at 635 nm) or fVII-VP (activation wavelength at 689 nm) conjugates, for treatment of human breast [12,17,18] and lung cancer [11] and wet macular degeneration [19] in preclinical studies. Our results showed that fVII-tPDT was selective and effective in vitro in killing angiogenic vascular endothelial cells and tumor cells that express TF as well as in vivo in treating breast and lung tumor xenografts in mouse models.…”
mentioning
confidence: 78%
“…The bottleneck of development of such dtPDT is to identify a common yet specific biomarker on both tumor compartments [10]. We [11][12][13][14] and several other groups [15,16] showed that tissue factor (TF) was selectively expressed by tumor angiogenic vascular endothelial cells and was also overexpressed by many types of cancer cells in melanoma, breast, lung and brain tumors. Thus we conclude that TF is a common yet specific biomarker and therapeutic target molecule for both the tumor cells and tumor neovasculature [10][11][12]17,18].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The combination immunotherapy can target different molecules on some or all major tumor compartments, including but not limited to the cancer cells, tumor neovasculature, cancer stem cells, MDSC, Treg and TAM, or ideally, target the same molecule that is commonly expressed by these major tumor compartments. In this regard, we believe that tissue factor (also known as coagulation factor III or CD142) is one of few such promising and common target molecules as it is commonly yet selectively expressed on many types of solid cancer cells as well as leukemic cells (21,22), tumor angiogenic vascular endothelial cells in vitro (23) and in vivo (22,(24)(25)(26) and cancer stem cells (27).…”
Section: Editorialmentioning
confidence: 99%